Antioxidant Activity of Goat Milk Yogurt Casein on Dioxin Intoxicated Rat Liver Function - Setianingrum, Ani; Padaga, Masdiana Chendrakasih (Veterinary Biomedical and Clinical Journal, 2019)
Dioxin is toxic contaminant which persistent in the environment. This compound bio-accumulate through food chain and generate adverse effect in human health. Oxidative stress due to dioxin exposure can interfere metabolism process and leads to the development of hepatotoxicity.The aim of this study was to asses the role of casein derived from goat milk yogurt in dioxin-intoxicated rat based on liver function parameters. Substances used were: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) diluted in corn oil and casein from goat milk yogurt. The study included 24 Wistar rats divided into 6 groups: (1) control group, (2) placebo group which given casein 600 mg/kg BW, (3) TCDD group given with TCDD 100 ng/kg BW, (4) group P1 given casein 300 mg/kg BW and TCDD, (5) group P2 given casein 600 mg/kg BW and TCDD, (6) group P3 given casein 900 mg/kg BW and TCDD. The respective dose were given orally for 21 days. Blood serum was collected for transaminases (ALT, AST) and Î³-glutamyl transferase (GGT) analysis. Based on serum transaminases activity, there were no significant change on AST and ALT level. Casein yogurt supplementation has significant effect on serum GGT level (p<0,05) and optimum dose was 600 mg/kg BW/day